Актуалізовані та нові слова й значення (матеріали до словника) - Тищенко, О. (Лексикографічний бюлетень, 2011)
In the article the ways of certification of register units and lexicographic sources in
the dictionary materials intended for identifying and fixing new words in the modern
Ukrainian language are analyzed. Special means are used, such as graphic characters indicating
some peculiarities of recording the words in other dictionaries as well as their
significance, functional use, etc. This encourages diachronic and synchronic observation
of the development of lexical units in language and in lexicographic interpretation.